PERAN ORANG TUA DALAM MEMELIHARA KESEHATAN GIGI DAN MULUT ANAK DI SEKOLAH DASAR ABDI AGAPE - Femala, Dian; E.D, Silva; Maryani, Yeni; Mahmiyah, Erma; Suryana, Budi (Poltekkes Kemenkes Banjarmasin, 2025)
The family environment, especially parents, plays a very big role in developing positive behavior towards dental and oral health. Parental involvement in developing positive behavioral patterns in maintaining oral health is implemented in their children in daily life, both directly and indirectly. The way to improve dental and oral health is for parents to pay attention to children's behavior regarding dental health and children's eating patterns that consume little cariogenic food. The aim of this research is to determine the role of parents in maintaining children's dental and oral health at Abdi Agape Elementary School. The method used in this research is a quantitative method with a descriptive approach. The total population was 260 parents using a sampling technique, namely purposive sampling with the Slovin formula, namely 72 respondents. The results of this study show that parents who carry out their role in maintaining children's dental and oral health are in the good category for the role of parents in regulating food diet as much as 88.89%, the good category for brushing children's teeth as much as 76.39%, and the bad category for brushing children's teeth. control of children's dental health was 51.39%. This research can be concluded that the majority of parents' role in maintaining children's dental and oral health in the role of parents in regulating food diet and the role of parents in brushing children's teeth have good criteria. Then the role of parents in controlling children's dental health has poor criteria. Keyword : Role of Parents, Maintaining Children’s, Dental and Oral Health